2019
DOI: 10.1111/jan.14124
|View full text |Cite
|
Sign up to set email alerts
|

Does the Partners in Health scale allow meaningful comparisons of chronic condition self‐management between men and women? Testing measurement invariance

Abstract: Aims To determine if the Partners in Health scale, pertinent to assessing patient chronic condition self‐management, operates equivalently for men and women. Background There are distinct gender‐based differences in self‐management behaviours and health perceptions. This may introduce non‐invariance in self‐report measures. Testing of measurement invariance is a recommended practice in nursing science to ensure robust metrics. Design A representative cross‐sectional population survey in South Australian. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In this study self-reported gender was not significantly associated with SMM or its dimensions, which suggests that self-perception of practices, knowledge and experiences learned from living with a condition are not mediated by gender perception [48]. The effect of gender on NCD self-management is not consistent and some studies have observed significant associations [39,41,49,50] while others have not [43,51,52], or an association that is exclusive to specific dimensions [38]. An explanation for these disparities in findings could be attributed to different cultural expectations associated with gender roles in the countries where studies were conducted.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In this study self-reported gender was not significantly associated with SMM or its dimensions, which suggests that self-perception of practices, knowledge and experiences learned from living with a condition are not mediated by gender perception [48]. The effect of gender on NCD self-management is not consistent and some studies have observed significant associations [39,41,49,50] while others have not [43,51,52], or an association that is exclusive to specific dimensions [38]. An explanation for these disparities in findings could be attributed to different cultural expectations associated with gender roles in the countries where studies were conducted.…”
Section: Discussionmentioning
confidence: 71%
“…In the present study, age, years of schooling level, number of diseases and self-rated health status were significantly associated with SMM, DK, SMDR, and MDM. These variables have been used in other research [38][39][40][41][42][43][44][45] aiming to understand the short-term modifiable effects on self-management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations